Air pollutants exposure and frequency of micronuclei (MN) among primary school children nearby industrial area - Muhamad Daud, Siti Aishah; Jalaludin, Juliana; Sopian, Nor Ashikin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Air pollutants that possessed genotoxic properties have the potential to induce genetic damage. Micronuclei (MN) frequency is used as an indicator for identifying potential genotoxic exposures. A comparative cross-sectional study was carried out among primary school children in a petrochemical industrial area (N=111, Kemaman) and a rural (N=65, Dungun) area in Terengganu. Methods: Validated questionnaires were distributed to obtain the respondents’ socio-demographic data, previous exposure and reported respiratory illness. The frequency of micronuclei was assessed in collected buccal mucosa samples of children. The air monitoring was also carried out at 6 selected schools. Results: Results from the statistical analysis carried out showed significant differences with p=0.001 for all parameters assessed between areas, which included ultrafine particles, UFP (z = -4.842), PM2.5 (z = -10.392), PM10 (z= -11.074) NO2 (z = -11.868), SO2 (z = -5.667), relative humidity (z = -5.587). The MN frequency was statistically significant with PM2.5 (χ2= 17.78, p=0.001) and PM10 (χ2= 15.429, p =0.001). The statistical analysis also showed a significant association between UFP and coughing (PR=2.965, 95% CI=1.069-8.225). The multiple logistic regression analysis showed that the main pollutants influencing MN frequencies were UFP and NO2 with UFP (PR=1.877, 95%CI= 1.174-3.002) and NO2 (PR=1.008, 95%CI= 1.001-1.015). Conclusion: This study demonstrated that exposure to air pollutants may increase the risk of respiratory illness and may induce MN formation among children.